Peran Desain dalam Pertunjukan Tumirah (Sang Mucikari) di Prodi Pendidikan Sendratasik Universitas Palangka Raya - Muhamad Romadoni; Jimy O Andin; Andi Arie Astuti; Cahyo Wahyu Darmawan (TAMUMATRA, 2023)
The role of design, as a visual art that most people think there is a dividing line between the art of motion and sound, will certainly be a new picture in understanding the interrelated relationship in the success of a performance. This is the background related to the research on the role of good design in a performance focused on the "Tumirah (Sang Mucikari)" performance performed at the University of Palangka Raya's Drama, Dance, and Music Education Study Program, with the aim of describing and analyzing the problems of the form and the creativity of the stage and the property used. The theory of two-dimensional and three-dimensional designs underlies the role of design in performance. The method used in this research is interpretative qualitative with case study studies. The results show that the role of design in the form of line, field, color, and space elements is inseparable from a performance. Design creativity that reduces some of its elements into imaginary elements and visualizes elements whose representation weight is high is a determining factor in explaining to the audience to be carried away in the atmosphere told in the performance story.